Influence of environmental factors on phytochemical compositions and antioxidant activity of Juniperus communis L - Purnima Rawat; Khashti Dasila; Mithilesh Singh; Jagdish Chandra Kuniyal (Discover Environment)
Abstract The present study focuses on the phytochemical content of Juniperus communis L. collected from different altitudinal locations in Uttarakhand, India. To the best of our knowledge, this is the first report which analyses the secondary metabolite contents, antioxidant potential, chlorophyll and carotenoid content of J. communis needles and their correlation with the environmental factors. The results showed variation in phytochemical content from different locations, with the highest total phenolic content of 42.80 ± 1.398 mg GAE/g DW estimated from JC3 (3891 m), flavonoid content of 2.47 ± 0.120 mg QE/g DW from JC4 (4065 m), and tannin content of 8.21 ± 1.445 mg TAE/g DW from JC4. The highest antioxidant activity determined by DPPH and ABTS assays were calculated as 36.97 ± 0.030 μg/mL and 518.78 ± 0.123 μg/mL in JC4 respectively while FRAP assay revealed highest antioxidative capacity of samples from JC2 (3507 m). The GC–MS analysis revealed the presence of around 35 compounds with communic acid, beta-Elemene, oplopanone, mome inositol, and spathulenol as the major compounds. In conclusion, elevation significantly influences the extraction yield, chlorophyll content, total polyphenol content, antioxidant activity, and chemical composition of the extracts.Soil properties, such as pH, moisture content, and nutrient availability, also played a role in these variations. Therefore, the findings suggest that environmental factors can significantly impact the bioactive potential of J. communis and highlight the importance of considering these factors in future research and applications.